Winners and losers in the global economy: Recent trends in the international division of labour and policy challenges - Peter Nunnenkamp (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
Globalised markets and production patterns offer favourable opportunities to raise world income. Yet globalisation also fuels conflicts about the distribution of welfare gains within and across countries. Various developing economies are poorly prepared to meet the challenge of fiercer competition on world goods and factor markets. In industrialised countries, low-skilled workers face mounting adjustment pressures. Multilateral trade liberalisation represents a "win-win strategy", with only a few possible exceptions in the short run. The neomercantilist notion that the removal of trade barriers is a concession to foreign trading partners is grossly fallacious. Income gains are mainly due to the countries' own liberalisation measures. Developing countries could have raised their share in world welfare gains if they had committed themselves more strongly to binding trade liberalisation during the Uruguay Round negotiations. Foreign trade and direct investment patterns reveal that the international division of labour is progressing not only in a regional context but also on a truly global scale. The opportunities for new competitors for foreign capital and technology transfers depend on domestic economic policies in the first place. Exogenous factors such as the recent revival of regional integration, autonomous locational decisions taken by multilateral corporations, and technological developments cannot be blamed for failures in benefiting from globalisation. The strikingly different economic performance of developing countries in globalised markets and production is clearly related to the progress made with respect to macroeconomic stabilisation, physical and human capital formation, and openness towards world goods and capital markets. Asian-type success stories could be repeated elsewhere, once governments have become aware that they can no longer pursue economic policies of their own liking. The Triad of the EU, Japan and the United States will come under fiercer adjustment pressure if more developing countries become involved in globalisation. Industrialised countries have little choice but to promote human capital formation in order to strengthen their comparative advantages in skill-intensive lines of production. Adjustment needs have been handled most effectively in Japan so far. By contrast, high unemployment in the EU, especially of low-skilled workers, appears to be the price that has to be paid for insufficient wage flexibility and structural change.
Keywords: 330; Internationale Arbeitsteilung; Globalisierung; Internationaler Wettbewerb; Direktinvestition; Wirtschaftliche Anpassung; Welt; Entwicklungsländer; Industriestaaten